Maternal Body Mass Index and Risk of Obstetric, Maternal and Neonatal Outcomes: A Cohort Study of Nulliparous Women With Spontaneous Onset of Labor. Issue 1 (23rd March 2022) - Dalbye, R.; Gunnes, N.; Blix, E.; Zhang, J.; Eggebø, T.; Nistov Tokheim, L.; Øian, P.; Bernitz, S.
Abstract : ( Acta Obstet Gynecol Scand . 2021;100:521–530. doi: 10.1111/aogs.14017. Epub November 27, 2020) Worldwide obesity and body mass index (BMI) have dramatically increased in the past few decades. As obesity can increase risk for serious health problems, understanding its impact on pregnancy and delivery is essential to improve patient care, labor outcomes, and health outcomes. Despite past work, there is still a need for studies examining impact of BMI on nulliparous women versus multiparous women and on induced and spontaneous onset of labor. This study focuses on nulliparous women with a singleton fetus in cephalic presentation with spontaneous onset of labor at term within the Ten-Group Classification System (TGCS) group 1. The aim of this study was to analyze those within TGCS group 1 and investigate the relational effect of early-pregnancy maternal BMI and obstetric, maternal, and neonatal outcomes.